2002
DOI: 10.1046/j.1365-2362.2002.0320s1021.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell antioxidant and iron status in alcoholic and nonalcoholic cirrhosis

Abstract: These results suggest that NTBI is more important than the decrease of antioxidant defences in inducing lipid peroxidation. NTBI may play a catalytic role in free radical reactions in the presence of cellular reductants such as NADPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…16 The decrease in DMT1 protein in the cirrhotic livers appears unlikely to play a primary role in the development of hemosiderosis, but may contribute to the increase in circulating levels of NTBI reported in cirrhotic patients. 36 In contrast to DMT1, we speculate that the decrease in Fpn in the cirrhotic livers may be mechanistically linked to the pathogenesis of hemosiderosis. Although Kupffer cells are the major cellular source of Fpn in liver, hepatocytes also express Fpn.…”
Section: Iron Regulatory Genes In Cirrhosismentioning
confidence: 73%
“…16 The decrease in DMT1 protein in the cirrhotic livers appears unlikely to play a primary role in the development of hemosiderosis, but may contribute to the increase in circulating levels of NTBI reported in cirrhotic patients. 36 In contrast to DMT1, we speculate that the decrease in Fpn in the cirrhotic livers may be mechanistically linked to the pathogenesis of hemosiderosis. Although Kupffer cells are the major cellular source of Fpn in liver, hepatocytes also express Fpn.…”
Section: Iron Regulatory Genes In Cirrhosismentioning
confidence: 73%
“…Nontransferrin bound iron was found to be higher in the high ferritin group and the antioxidants GPx and SOD were lower which suggests elevated ferritin levels might represent elevated NTBI levels and the subsequent reduction in antioxidant capacity. However, there are conflicting reports showing no significant relationship between NTBI and serum iron parameters (Harrison et al, 1996;Domenica Cappellini et al, 2000;Fiorelli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…GSH levels fall to 85% of total (from normal physiological levels of 97–99%) with a concomitant rise in GSSG to about 15% (37). We did not separately estimate GSSG, because erythrocyte GSSG is minimally affected by cirrhosis because of chronic hepatitis C and B, and accounts for only 3% of total GSH (38). Jain et al (18) have demonstrated no significant difference in GSSG between noncirrhotic and cirrhotic CHC patients.…”
Section: Discussionmentioning
confidence: 99%